Human–Computer Interaction and Digital Advertising Effectiveness: A Systematic Literature Review of Visual Attention, Interface Design, and Persuasion - Patrissia, Ressa Uli; Basuki, Pritha Ayodya; Husni, Mochamad (Dinasti Research, 2026)
Digital advertising is increasingly embedded within contemporary human–computer interaction (HCI) environments, where advertisements function not only as persuasive messages but also as structural elements of digital interfaces. Despite the rapid growth of online advertising, research examining how interface design influences advertising effectiveness remains fragmented across HCI, communication science, and marketing. This study synthesizes interdisciplinary research on how HCI-related interface variables affect visual advertising attention, avoidance, and persuasion outcomes. A systematic literature review following the PRISMA 2020 framework was conducted using four major databases: Web of Science, Scopus, PubMed, and the ACM Digital Library. The review covers peer-reviewed studies published between 2000 and 2025 that combine HCI methodologies—such as eye-tracking, usability evaluation, interaction logging, and user experience measurement—with advertising outcomes including attention, recall, persuasion, and avoidance. A total of 118 studies met the inclusion criteria and were analyzed using narrative synthesis. The findings indicate that advertising effectiveness is strongly shaped by interface-level variables including visual complexity, animation, interactivity, aesthetic congruence, and user task context. Visual attention operates through a dual-pathway mechanism in which bottom-up visual salience interacts with top-down goal-directed browsing behavior, explaining phenomena such as banner blindness. The review highlights the need for stronger theoretical integration between HCI and communication-based persuasion frameworks.